INVESTIGATION OF HEAVY METAL CONCENTRATIONS IN SOIL CAUSED BY WILD STORAGE DUMPSITE IN KASTAMONU CITY - SAVACI, Gamze; ÖKSÜZ, Çağatay (Turkish Journal of Forest Science, 2020)
The aim of this study was to reveal the effects of domestic dumpsite on the some soil chemical properties in the surface soils in Kastamonu city. The soil samples were collected from the 5 different distances namely; Very adjacent (VA), Adjacent (A), Middle (M), Far (F) and Very far (VF). The results showed that the accumulation of heavy metal in the soil varied significantly with the distances. Among the heavy metals, the concentrations of Co, Cr, Cu (only A and VA), Zn (only A and VA), Ni (except for M) exceeded the Maximum Allowable Limit (MAL) for Turkey values. However, the concentrations of Mo, Pb and Cd were below the MAL limit values. When all results are considered, it can be stated that the waste dumpsites can negatively affect the environment. Therefore, we make sure that the dumped materials should be concentrated and recycled in order to decrease the amount of heavy metals in the dumpsites and in the soils around the dumpsites. In addition, phytoremediation, which is all the remediation technique available for metal contaminated soils, is the most costly, environmentally friendly and easy to apply. Phytoremediation can be used to remove, displace or reduce contaminants from soil by using plants that hyperaccumulate these contaminants.
Keywords: 13. Climate action; 6. Clean water